Perpetual Betterising: - Brett Chulu (Grounded Theory Review: An International Journal)
Clayton Christensen’s theory of disruptive innovation has a partial ancestry in classic grounded theory (CGT), anchored in the original methodological ideas of inductive theory-building, categorisation, formal theory, and modifiability. The locus of disruptive innovation theory resides at the nexus of sociology and economics. The inescapable sociological pedigree of this theory naturally lends itself to CGT analysis. Christensen’s theory cores out with a variable of perpetual betterising recurrently resolving co-dependent main concerns held by a firm’s dominant coalition and the recipients of organisation-created value. Christensen’s theory is upgraded by employing reconstructive processes to rid it of margins of error (conceptual-descriptive syncretism) and margins of terror (unintended imposition and pre-conceiving). Perpetual betterising is a multivariatised conceptual model. The categories comprising perpetual betterising lend themselves to threading together by a biological species evolution-invasion theoretical code. Through the lenses of perpetual betterising, this paper explores long-standing and current debates around disruptive innovation.